Electroencephalography of response inhibition tasks: Functional networks and cognitive contributions - Huster, René J.; Enriquez-Geppert, Stefanie; Lavallee, Christina F.; Falkenstein, Michael; Herrmann, Christoph S. (International journal of psychophysiology, 2013)
Response inhibition paradigms, as for example stop signal and go/no-go tasks, are often used to study cognitive control processes. Because of the apparent demand to stop a motor reaction, the electrophysiological responses evoked by stop and no-go trials have sometimes likewise been interpreted as indicators of inhibitory processes. Recent research, however, suggests a richer conceptual background. Evidence denotes an association of a frontal-midline N200/theta oscillations with premotor cognitive processes such as conflict monitoring or response program updating, and an anterior P300/delta oscillations with response-related, evaluative processing stages, probably the evaluation of motor inhibition. However, the data are still insufficient to unambiguously relate these electroencephalographic measures to specific inhibitory functions. Beta band activity only recently has become a focus of attention in this task context because of its association with the motor system and regions involved in inhibitory control. Its functional role in response inhibition tasks needs further exploration though. Hence, as things stand, any deduction of differences regarding actual inhibitory capabilities or loads between subject groups or conditions based on electroencephalographic measures has to be treated with caution. ► EEG studies of stop signal and go/no-go tasks are reviewed. ► N200/frontal-midline theta seem to be associated with premotor processes. ► P300/delta oscillations reflect response-related, evaluative processing stages. ► EEG-indicators of proper inhibitory functions are undetermined.